METHOD OF LIQUID CHROMATOGRAPHY – TANDEM MASS-SPECTROMETRY FOR ENNIATINS A, A1, B, B1 AND BEAUVERICIN DETERMINATION IN WINTER WHEAT - Pylypenko, Oksana; Baranovsky, Mikhail (Proceedings of National Aviation University (archive), 2018)
Objective: the aim of this study is to develop and validate a method of liquid chromatography – tandem mass-spectrometry for determination Fusarium mycotoxins namely eniatins A, A1, B, B1 and beauvericin. Methods: this article considers an analytical method based on high-performance liquid chromatography coupled with tandem mass-spectrometry for quick separation, identification, and quantification of mycotoxins in one sample. Results: it is proved that proposed method is accurate, selective, and rapid for identification and quantification of law-molecular weight compound accumulated in grain in small amount. Discussion: the effectiveness of liquid chromatography – tandem mass-spectrometry for determination of low concentrated mycotoxins in samples is confirmed. The validation ranges for analysts are compared to similar aimed researches of past years.